HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA-TANGAN DENGAN KEMAMPUAN SERVIS FOREHAND TENIS MEJA PADA ATLET JUNIOR SEKOLAH TENIS MEJA (STM) PRATAMA PEKANBARU - Syaiful Efendi; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The problems obtained are: some athletes have not been optimal in doing table tennis service, this can be seen in the ball of service results that are involved on the net, out of the field, their height is easily dismash by their opponents and the timing of the punch hits the ball so the ball does not go fast . The purpose of this study is to find out whether there is a wrist flexion relationship and eye-hand coordination with table tennis forehand service skills. The population in this study was a male junior athlete in table tennis at the Pratama Pekanbaru Table Tennis School (12 people). The sampling technique in this study was a total sampling technique. This means that the entire population is sampled, so that the sample in this study amounted to 12 people. The instruments in this study were wrist flexibility tests, tennis ball catch test and table tennis forehand service ability test. The data obtained are analyzed using product moment correlation. Based on the results of the research that the author has described in the previous chapter, then conclusions can be taken as follows. From the results obtained wrist flexibility has a relationship with the forehand service ability in Junior table tennis athletes STM Pratama Pekanbaru. From the results obtained eye and hand coordination has a relationship with the forehand service ability in Junior table tennis athletes STM Pratama Pekanbaru. There is a joint relationship between wrist flexibility and eye and hand coordination on forehand service ability in Junior table tennis athletes STM Pratama PekanbaruKeywords: Flexibility of the Wrist, Eye and Hand Coordination, Forehand Service Ability